MANAJEMEN RISIKO PROYEK PENGEBORAN UNTUK PRODUKSI HULU MINYAK DAN GAS PADA PT XYZ - Achsana S, Takayyasa
PT XYZ focuses on the exploitation of natural resources through a range of activities, including drilling, construction of transportation and storage infrastructure, and processing and production. In 2022, the company failed to achieve its oil and condensate production target, achieving only 79.1% on Y field, where PT XYZ acts as lifting operator. In 2023, two projects were undertaken in Field Y, namely Drilling Project A and Drilling Project B. Drilling Project A failed, while Drilling Project B, although successful, was not perfect. The results of both projects became lessons learned for PT XYZ for Drilling Project C which will commence in 2025. PT XYZ's Development and Planning Manager stated that the failure was suspected to be caused by the lack of effectiveness of risk mitigation, lack of regular evaluation and update of the risk register, and selection of suboptimal risk responses. Therefore, a new and more effective risk management design was required. Risk management is conducted based on the ISO 31000 framework: 2018. The scope, context, and criteria of the risk management design were defined. Risks were identified using Risk Failure Mode Effect and Analysis (RFMEA), resulting in 88 risks based on the Work Breakdown Structure. Risks were qualitatively assessed for severity, occurrence, and detection, then calculated to determine risk prioritization using Pareto for Risk Score Value and Risk Priority Number, and based on Cost Severity, resulting in two types of Risk Map showing 26 overlapping risks. Most of the risks, namely 16 risks, were classified as medium priority. Furthermore, 6 high-priority risks were identified as top priorities to be addressed, namely the risks of unidentified drilling surprise, failed procurement time and cost design, over-estimated tender estimate, obtaining drilling operation permit, local community mobilization constraints, and tool pinching and mud circulation loss. Proposed response plans were developed for 26 prioritized risks, both high and medium, with mitigate or accept type responses. Afterward, an examination of the residual risks was conducted, where 3 risks were found to still fall into the medium priority category, with an estimated maximum response and contingency cost of USD1.885.000. The estimated cost is expected to save the cost impact to a maximum of USD51.365.000. The economic impact of the risk management recommendation is the potential cost savings and reduction in losses due to unexpected events or project failure. However, PT XYZ needs to further review aspects of the proposal that involve further evaluation of the effectiveness of the proposed response and the company's readiness to implement. The social impacts of the design include reducing the risk of occupational accidents, environmental damage, or other negative impacts on local communities. By understanding these risks, companies can improve community relations and create a safer working environment.